Kisspeptins and RFRP-3 Act in Concert to Synchronize Rodent Reproduction with Seasons - Simonneaux, Valerie; Ancel, Caroline; Gauer, François; Poirel, Vincent-Joseph (Frontiers in Neuroscience, 2013)
Seasonal mammals use the photoperiodic variation in the nocturnal production of the pineal hormone melatonin to synchronize their reproductive activity with seasons. In rodents, the short day profile of melatonin secretion has long been proven to inhibit reproductive activity. Lately, we demonstrated that melatonin regulates the expression of the hypothalamic peptides kisspeptins (Kp) and RFamide-related peptide-3 (RFRP-3), recently discovered as potent regulators of GnRH neuron activity. In the male Syrian hamster, Kp expression in the arcuate nucleus is down-regulated by melatonin independently of the inhibitory feedback of testosterone. A central or peripheral administration of Kp induces an increase in pituitary gonadotropins and gonadal hormone secretion, but most importantly a chronic infusion of the peptide reactivates the photoinhibited reproductive axis of Syrian hamsters kept in short day conditions. RFRP-3 expression in the dorsomedial hypothalamus is also strongly inhibited by melatonin in a short day photoperiod. Although RFRP-3 is usually considered as an inhibitory component of the gonadotropic axis, a central acute administration of RFRP-3 in the male Syrian hamster induces a marked increase in gonadotropin secretion and testosterone production. Furthermore, a chronic central infusion of RFRP-3 in short day-adapted hamsters reactivates the reproductive axis, in the same manner as Kp. Both Kp and RFRP-3 neurons project onto GnRH neurons and both neuropeptides regulate GnRH neuron activity. In addition, central RFRP-3 infusion was associated with a significant increase in arcuate Kp expression. However, the actual sites of action of both peptides in the Syrian hamster brain are still unknown. Altogether our findings indicate that Kp and RFRP neurons are pivotal relays for the seasonal regulation of reproduction, and also suggest that RFRP neurons might be the primary target of the melatoninergic message.